Smiling Down the Line : Info-Service Work in the Global Economy - Russell, Bob, 1950- (Book collections on Project MUSE., 2009)
Smiling Down the Line theorizes call centre work as info-service employment and looks at the effects of ever-changing technologies on service work, its associated skills, and the ways in which it is managed.